(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article provides an overview of nouns and their grammatical categories, emphasizing their pivotal role in sentence structure and meaning. It explores key categories such as number, gender, case, definiteness, countability, and animacy, offering examples from English and other languages to illustrate their diversity. The piece highlights how these categories influence the way nouns interact with other words in a sentence and shape linguistic expression. Additionally, the article underscores the cultural and cognitive significance of these grammatical features, making it a valuable resource for linguists, language learners, and grammar enthusiasts